Theoretical bases of political socialization models (Journal of Philosophy Culture and Political Science, 2019)
In given article the types and models of political socialization are considered. Genesis and formation of the term is one of the pressing issues in current political studies. From the one side, there is public necessity in political development of the individual, from the other side alienation of individual from the government and its institutions take are taking place. Development of interdisciplinary studies contributed to the revealing of essence of the models of political socialization. Dynamics of current political processes is another reason for deep studying of processes of political socialization. Authors emphasize the importance of interdisciplinary approach of given processes. Keywords: political socialization, concept, model, institute, process.